ANALISIS TRANSAKSI BISNIS INTERNASIONAL DALAM PRESPEKTIF HUKUM DAN EKONOMI PADA PERDAGANGAN GLOBAL MELALUI STUDI KASUS SENGKETA EKSPOR UDANG INDONESIA KE AMERIKA SERIKAT - Achmad Fahri (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze international business transactions from legal and economic perspectives in global trade through the shrimp export dispute between Indonesia and United States. The background of this research is based on the increasing complexity of international trade, which often leads to conflicts due to differences in national interests. The dispute arose from allegations of subsidies that were considered to create unfair trade practices. This study applies a normative juridical approach using secondary data obtained through library research. The data are analyzed qualitatively by examining legal regulations and economic conditions underlying the dispute. The results indicate that the subsidy allegations were not proven to violate international trade law since the subsidy level remained below the established threshold. From a legal perspective, this case highlights the importance of interpreting legal norms in determining the validity of trade policies. From an economic perspective, the dispute reflects price competition and production efficiency in the global market. The dispute was resolved through bilateral mechanisms without involving formal procedures of the World Trade Organization. The outcome positively contributed to the stability of trade relations between the two countries. This study concludes that international business transactions are closely related to the interaction between legal and economic aspects. Trade disputes are a consequence of conflicting interests that require fair and transparent resolution mechanisms.